2014
DOI: 10.1016/j.virol.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 E6 and E6AP differentially cooperate to stimulate or augment Wnt signaling

Abstract: The present study investigated the roles of E6 and E6AP in the Wnt pathway. We showed that E6 levels are markedly reduced in cells in which Wnt signaling is activated. Coexpression of wild-type or mutant E6AP (C820A) in Wnt-activated cells stabilized E6 and enhanced Wnt/β-catenin/TCF transcription. Expression of E6AP alone in nonstimulated cells elevated β-catenin level, promoted its nuclear accumulation, and activated β-catenin/TCF transcription. A knockdown of E6AP lowered β-catenin levels. Coexpression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…The phosphomimetic UBE3A T485E mutant, which impairs UBE3A ubiquitin ligase activity, was much less effective at stimulating Wnt pathway activation. Consistent with a previous study (40), UBE3A-LD did not activate the pathway ( Fig. 2A and 2B), indicating that UBE3A ubiquitin ligase activity is re-UBE3A activates Wnt signaling quired to stimulate Wnt pathway activation.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The phosphomimetic UBE3A T485E mutant, which impairs UBE3A ubiquitin ligase activity, was much less effective at stimulating Wnt pathway activation. Consistent with a previous study (40), UBE3A-LD did not activate the pathway ( Fig. 2A and 2B), indicating that UBE3A ubiquitin ligase activity is re-UBE3A activates Wnt signaling quired to stimulate Wnt pathway activation.…”
supporting
confidence: 92%
“…S1E) (55,56), and Wnt signaling regulates proliferation and differentiation of neuronal progenitors (57,58). Our study, and the work of others (40)(41)(42), firmly places UBE3A within the Wnt signaling pathway, and provides fundamental new insights into how excess UBE3A could impair brain development and increase risk for autism.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Rampias further demonstrated that repressed expression of HPV16 E6 and E7 reduced nuclear β‐catenin levels in HPV‐positive cells, whereas expression of these oncogenes enhanced β‐catenin‐TCF/LEF‐mediated transcription, suggesting a critical role of HPV16 E6 and E7 in Wnt signalling activation. Lichtig further demonstrated that HPV16 E6 in cooperation with E3 ubiquitin ligase E6AP increased β‐catenin expression and enhanced β‐catenin‐TCF transcription .…”
Section: Viruses Implicated In Human Cancer Developmentmentioning
confidence: 95%